DDoS attacks detection based on link character - SUN Hong-jie; FANG Bin-xing; ZHANG Hong-li (Tongxin xuebao)
A new method based on link character was proposed for DDoS attacks detection.Maximum likelihood estima-tion was used to estimate the distribution of link character.SOM neural network is used for link activity profile learning and anomaly link detection.Experiment results indicate that the technique is effective and of a definite practicability.It has a further develop potential for DDoS attacks detection.